The Right to Remain Silent vs. Defendant Statements: Examining Indonesia's New Criminal Procedure Code - Dede Kania; Tia Ludiana; Agi Attaubah Hidayat (Faculty of Law Universitas Jenderal Soedirman, 2026)
Article 142 of the New Criminal Procedure Code introduces the right to remain silent, yet it conflicts with Article 235, which continues to recognize defendant statements as valid evidence. This normative discrepancy creates legal uncertainty regarding the protection of suspects' and defendants' rights during the evidentiary process in Indonesia's judicial system. The aim of this research is to examine the existence of Defendant Statements in Indonesia's New Criminal Procedure Code in light of the Right to Remain Silent principle. The research adopts a normative legal method supported by a comparative approach in the United States of America and the Netherlands. It analyzes statutory provisions and compares them with legal systems that firmly uphold the privilege against self-incrimination. The findings demonstrate a clear contradiction between Article 142, which guarantees the Right to Remain Silent, and Article 235, which still recognizes Defendant Statements as valid evidence. This inconsistency creates legal uncertainty and undermines the effective protection of suspects’ and defendants’ rights during the evidentiary process from a critical perspective, suggesting that New Criminal Procedure Code has not fully embraced the principle of due process. It also creates the potential for abuse of power, particularly in practices that pressure defendants into providing statements. This study, therefore, proposes harmonising Articles 142 and 235 to ensure coherence between human rights principles and evidentiary mechanisms. The study contributes to this by offering a doctrinal and comparative framework to reinforce the implementation of the non-self-incrimination principle within Indonesia's criminal justice system.